2018
DOI: 10.1016/j.stem.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Signaling between Glioblastoma Stem Cells and Differentiated Tumor Cells Promotes Malignant Progression

Abstract: Glioblastoma is the most lethal primary brain tumor; however, the crosstalk between glioblastoma stem cells (GSCs) and their supportive niche is not well understood. Here, we interrogated reciprocal signaling between GSCs and their differentiated glioblastoma cell (DGC) progeny. We found that DGCs accelerated GSC tumor growth. DGCs preferentially expressed brain-derived neurotrophic factor (BDNF), whereas GSCs expressed the BDNF receptor NTRK2. Forced BDNF expression in DGCs augmented GSC tumor growth. To dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
188
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(197 citation statements)
references
References 73 publications
(93 reference statements)
5
188
1
3
Order By: Relevance
“…4,5 Understanding which factors promote stemness and treatment resistance of glioma cells is of intense interest in developing new therapies in glioma. A large number of studies over the past decade have established that there is considerable plasticity in glioblastoma cell phenotypes, [6][7][8][9][10][11] that stem cell characteristics can be acquired by non-stem-like cells, 8,9,[12][13][14][15] and that microenvironmental cues such as hypoxia, 16 extracellular matrix proteins, [17][18][19][20][21][22][23][24][25] or growth factors secreted by stromal cells [26][27][28] may be sufficient to induce tumor cell stemness and therapeutic resistance. The role of the microenvironment in regulating tumor stemness is further supported by the finding that stem-like tumor cells are enriched in specific tumor niches; in GBM, primarily the perivascular niche (PVN) and hypoxic compartments.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Understanding which factors promote stemness and treatment resistance of glioma cells is of intense interest in developing new therapies in glioma. A large number of studies over the past decade have established that there is considerable plasticity in glioblastoma cell phenotypes, [6][7][8][9][10][11] that stem cell characteristics can be acquired by non-stem-like cells, 8,9,[12][13][14][15] and that microenvironmental cues such as hypoxia, 16 extracellular matrix proteins, [17][18][19][20][21][22][23][24][25] or growth factors secreted by stromal cells [26][27][28] may be sufficient to induce tumor cell stemness and therapeutic resistance. The role of the microenvironment in regulating tumor stemness is further supported by the finding that stem-like tumor cells are enriched in specific tumor niches; in GBM, primarily the perivascular niche (PVN) and hypoxic compartments.…”
Section: Introductionmentioning
confidence: 99%
“…We chose these receptors based on their important roles in GBM biology. EGFR is a major driver of malignancy (Thorne et al, 2016), while p75NTR facilitates cell infiltration and its ligand is implicated in GBM progression (Johnston et al, 2007;Wang et al, 2018). We found that both EGFR and p75NTR were co-segregated with the PMGFP ACD reporter ( Fig.…”
Section: Acd Co-enriches Egfr and P75ntr Which Promotes Self-renewalmentioning
confidence: 68%
“…The net fitness of the tumor cannot be determined solely by that of tumorigenic cells such as CSCs or the most proliferative cells in the tumor; a dynamic interaction among the different types of tumor cells and their interaction with stromal cells are also critical factors. Furthermore, reciprocal crosstalk between CSCs and more differentiated tumor cells may contribute to tumor growth (Silver and Lathia, 2018;Wang et al, 2018). In this context, ACD may contribute to overall tumor growth by generating heterogeneous populations of cells that form a mutually beneficial paracrine network involving BDNF, a p75NTR ligand.…”
Section: Discussion Of Key Findingsmentioning
confidence: 99%
“…Serum (FBS) is a variable and as yet undefined media supplement that contains many different soluble factors such as growth factors, hormones and vitamins, with potential to contribute to cell growth and survival (Brunner et al, ). Since the discovery that SF conditions more faithfully retained the original phenotype of GBM cells in culture, serum has often been used experimentally to demonstrate the differentiation potential and loss of GSC characteristics of SF established GSC cultures (Lee et al, ; Singh et al, ; Wang et al, ). The fact that ESCs could be maintained under serum conditions is not unexpected since this for decades was the standard GBM cell culture method, and the majority of our SFCs also had a maintainable sister SC.…”
Section: Discussionmentioning
confidence: 99%